Islamic Philanthropy and the Qur’anic Approach to Scarcity: Wealth Redistribution as a Solution - Muhammad Faizul, Naqibah (Universitas Darussalam Gontor, 2025)
This study examines the problem of scarcity as understood in conventional economics and compare it with its understanding in Islamic economics. In addition, explore how Islamic Philanthropy become the ultimate weapon in mending many conventional economic problems including scarcity. To accomplish these objectives, a qualitative methodology, including doctrinal library research and comparative analysis, was employed to examine both frameworks. The findings reveal that Islamic economics recognised only relative scarcity, emphasizing resource sufficiency and moral responsibility. In addition, Islamic philanthropy has demonstrated its effectiveness in resolving many conventional economic issues, shedding light on its potential for promoting economic justice and social welfare.